2005
DOI: 10.1057/palgrave.jors.2601927
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the human development index via data envelopment analysis

Abstract: To consider different aspects of life when measuring human development, the United Nations Development Program introduced the Human Development Index (HDI). The HDI is a composite index of socioeconomic indicators that reflect three major dimensions of human development: longevity, knowledge and standard of living. In this paper, the assessment of the HDI is reconsidered in the light of data envelopment analysis (DEA). Instead of a simple rank of the countries, human development is benchmarked on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(136 citation statements)
references
References 17 publications
2
123
0
11
Order By: Relevance
“…Since the first DEA-based CI model proposed by Melyn and Moesen (1991), various indexes have been developed by using the DEA technique. The environmental performance index [Färe et al, 2004], the human development index [Despotis, 2005], the macroeconomic performance index [Ramanathan, 2006], the sustainable energy index [Zhou et al, 2007], the internal market index [Cherchye et al, 2007], the technology achievement index [Cherchye et al, 2008], and the road safety performance index [Hermans, 2009], are examples among others. Furthermore, as a valuable extension of the basic DEA-based CI model, Shen et al (2011; proposed a generalized multiple layer DEA model (MLDEA) and a MLDEA-based CI model, which took the layered hierarchy of indicators into account.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first DEA-based CI model proposed by Melyn and Moesen (1991), various indexes have been developed by using the DEA technique. The environmental performance index [Färe et al, 2004], the human development index [Despotis, 2005], the macroeconomic performance index [Ramanathan, 2006], the sustainable energy index [Zhou et al, 2007], the internal market index [Cherchye et al, 2007], the technology achievement index [Cherchye et al, 2008], and the road safety performance index [Hermans, 2009], are examples among others. Furthermore, as a valuable extension of the basic DEA-based CI model, Shen et al (2011; proposed a generalized multiple layer DEA model (MLDEA) and a MLDEA-based CI model, which took the layered hierarchy of indicators into account.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of a unit is defined as the weighted sum of its outputs divided by a weighted sum of its inputs. As Despotis (2005) [40] underlines, the weights for inputs and outputs are estimated by a linear programming so as to maximize the relative efficiency of each unit. Farrell (1957) [41] introduced the concept of "best practice frontier", which delineates the technological limits of what a country can achieve with a given level of resources.…”
Section: Dea Studies In the Air Transportmentioning
confidence: 99%
“…the CI values are independent of the units in which the constituent sub-indicator values are measured [4]. The DEA was already applied in the field of CI providing alternative weighting systems ( [11], [8], [3], [4], [22]). It was reported that the use of DEA overcomes some key limitations, the undesirable dependence of final results from the preliminary normalization of sub-indicators, and from subjectivity in weighting [4].…”
Section: Composite Indicatorsmentioning
confidence: 99%
“…Two types of sub-indicator share restrictions were imposed: a proportional sub-indicator share restrictions (8) and restrictions pertaining to category shares (9). When applying the min-max normalization and the general normalization (7), it is possible to set only the upper bound for each proportional sub-indicator share (8). This upper bound was set to 50% higher than the weights determined by the government decree, .…”
Section: The Benefit-of-the-doubt Approach and Simple Linear Optimizamentioning
confidence: 99%